Pengaruh Efektivitas Pengendalian Internal, Tekanan Finansial dan Personal Culture terhadap Kecenderungan Kecurangan Akuntansi pada Lembaga Perkreditan Desa (LPD) Se-Kecamatan Denpasar Selatan - Marindhea, Varlinka; Indraswarawati, Sang Ayu Putu Arie; Yuniasih, Ni Wayan (UNHI Press, 2025)
Accounting fraud in LPDs is a form of fraud that is deliberately carried out to obtain personal gain which causes losses to customers, stakeholders and local communities without the injured party realizing it. The purpose of this research is to analyze the influence of the effectiveness of internal control, financial pressure and personal culture on the tendency of accounting fraud in LPDs throughout South Denpasar District. The study used a sample of 30 respondents selected through purposive sampling and collected data using a questionnaire. Data analysis involved multiple linear regression analysis, and hypothesis testing through the t-test. The findings of the study indicate that internal control and personal culture have a notable and unfavorable impact on the inclination towards accounting fraud. On the other hand, financial pressure has a noticeable and favorable impact on the tendency for accounting fraud. To ensure transparency and accountability in financial tasks, it is advisable to reinforce internal control by implementing the current policies and procedures.